The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.5194/aab-54-83-2011
|View full text |Cite
|
Sign up to set email alerts
|

Growth and development of young game pheasants (<i>Phasianus colchicus</i>)

Abstract: Fifty game pheasants were kept to 8 weeks in confinement housing and later maintained outdoors in a partially roofed aviary. Pheasants received commercial feed mixtures ad libitum. Body weight and dimensions were determined every 4 weeks. Ten pheasants were selected for slaughter at the end of 18 and 20 weeks each. After slaughter, their heads, shanks, feathers, blood, inedible viscera and major internal organs were weighed and digestive tract separated and measured. The carcasses were dissected. Higher body w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 10 publications
4
17
0
2
Order By: Relevance
“…The length of the fattening period also differs in the literature. Kokoszynski et al (2011) report 16-20 weeks, and the carcass yield between 69.7 and 73.7%, and similar conclusions were also reached by Adamski and Kuzniacka (2006). However, Sarica et al (1999) used a shorter fattening period of 13, 14 and 15 weeks with a slaughter yield of 74.19%, 73.13% and 74.3%, respectively.…”
Section: Pheasants Fatteningsupporting
confidence: 84%
“…The length of the fattening period also differs in the literature. Kokoszynski et al (2011) report 16-20 weeks, and the carcass yield between 69.7 and 73.7%, and similar conclusions were also reached by Adamski and Kuzniacka (2006). However, Sarica et al (1999) used a shorter fattening period of 13, 14 and 15 weeks with a slaughter yield of 74.19%, 73.13% and 74.3%, respectively.…”
Section: Pheasants Fatteningsupporting
confidence: 84%
“…The difference between the arithmetic means of lower thigh length in quail of different ages was not significant. In game pheasants, Kokoszyński et al (2011) showed lower thigh length to increase up to 12 weeks of rearing, from 7.4 cm to 13.4 cm in males and from 7.2 cm to 12.1 cm in females. Shank length (Table 1) in the quail analysed at 35 and 45 days was the same (3.7 cm).…”
Section: Resultsmentioning
confidence: 93%
“…The length of trunk with neck and the length of trunk were lower in 35-day-old compared to 45-day-old birds, with significant differences in the mean values of these traits (P≤0.05). A study with game pheasants (Kokoszyński et al, 2011) showed the length of trunk with neck to increase between 4 and 20 weeks of age, from 15.3 cm to 29.6 cm in males and from 15.0 cm to 26.9 cm in females.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing numbers of pheasants are also raised commercially to be slaughtered for meat (19,22). Captive-reared pheasants are frequently kept in large flocks in aviaries (13) or, particularly during the laying period, in cage systems (15,58,61).…”
Section: Introductionmentioning
confidence: 99%